The Mental Health Status of College Students in Bangladesh and Associated Factors - Md. Sanaul H. Mondal (Dr. Sulaiman Al Habib Medical Journal)
Introduction: Student protests are a widespread phenomenon globally. Recently, Bangladeshi students engaged in a nationwide protest, which lasted for a month. Such protests may have adverse effects on individual’s mental health, potentially increasing the risk of anxiety and depression. This study aimed to assess the mental health status of college students following the July Revolution of 2024 in Bangladesh. Methods: Data for this study were collected through a self-reported online questionnaire. The General Health Questionnaire (GHQ-12) was employed to assess the mental health status of participants. Statistical analyses were performed using SPSS version 26, and bivariate and multivariate logistic regressions were performed. Results: A total of 125 students participated in this study, of whom 35 (28%) were female and 90 (72%) were male. The average age of the respondents was 18.31 years (SD = 1.27). Clinically significant psychological distress was observed in 114 (91.2%) participants. A higher proportion of females (97.1%) experienced psychological distress compared to males (88.9%). Loss of sleep due to worry was associated with respondents’ age and enrollment in Bengali-medium educational institutes. Similarly, loss of confidence was more prevalent among female students, and the age of respondents was positively associated with the loss of confidence. Conclusion: The mental health status of college students is a matter of concern. There is an urgent need for targeted mental health interventions to promote the well-being of college students.